Effectiveness Of Mobile Website-Based SIPALING KB On The Selection Of Contraceptive Methods - Ryzky Diah Anggraini; Dwi Riyan Ariestantia; Nuuva Yusuf (Sean Institute, 2023)
Counseling is a very important aspect of family planning (KB) services. By doing counseling, it means that the officer helps in choosing and deciding the type of contraception to be used according to the client's choice. An estimated 225 million women in developing countries wish to delay or terminate fertility but do not use any contraceptive method due to limited choice of contraceptive method and experience of side effects. The SIPALING KB Mobile Website is a development of a family planning counseling method that can be accessed easily anytime and anywhere by prospective family planning acceptors using only a smartphone. In its design, SIPALING KB has a knowledge base for a particular domain and is designed based on a problem-solving model from an expert, making it easier for users to obtain information and determine early on which contraceptive method to use. The purpose of this research is to develop a counseling system through a mobile website with the name SIPALING KB which will assist prospective acceptors in determining which contraception to use. The research method used in this study was an experimental method with a randomized control group pretest-posttest design. With the group that was given the mobile website for family planning and the group that was given counseling using leaflets